Pengendalian Helminthiasis pada Peternakan Ayam Petelur Tradisional di Kabupaten Magetan, Provinsi Jawa Timur - Aji Winarso (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Optimization of resources is very important in achieving high productivity laying birds in order to support the fulfillment of consumption and ensure the economic sustainability of the farm. Laying poultry farms can not be separated from the variable costs, and the highest cost is bird’s feed. Therefore, the main indicator is feed conversion ratio (FCR), which depicts the conversion of feed into eggs. Most of the poultry farm business in Indonesia is a small-medium scale traditionally managed farms, so some aspects of farm management inhibits optimal performance. One of the important parts that can lead to a waste of resources ranch is about a lack of attention to parasite control. Parasites disadvantage due to being the host competitors in getting nutrients. This researchattempts to study the problem of controlling cestodes at poultry farm folk in Magetan, East Java. The results showed high cestode infection rate, with prevalence reaching 100% at postmortem. The main problems found were a low frequency of cleaning dirt, the host control between (flies) is not maximized, and the treatment of intestinal worms (deworming) with drugs that are not appropriate.